2001
DOI: 10.1046/j.1468-3148.2001.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Ageing – Adults with Intellectual Disabilities: Physical Health Issues

Abstract: This report has been prepared by the Ageing Special Interest Research Group of the International Association for the Scientific Study of Intellectual Disabilities (IASSID) in collaboration with the Department of Mental Health and Substance Dependence and the Programme on Ageing and Health, World Health Organization (WHO), Geneva, Switzerland, and all rights are reserved by the above mentioned organization. The document may, however, be freely reviewed, abstracted, reproduced or translated in part, but not for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 119 publications
1
139
0
4
Order By: Relevance
“…15 These studies have also shown differences in the nature and extent of stigma attached to the various psychiatric illnesses by the different cadres of medical health workers. [15][16][17][18][19][20][21][22] This study therefore aimed to determine the knowledge of and attitude towards mental illness among hospital staff in general medical facilities. This information would be useful in the formulation of policy for training, management and service delivery on mental health issues in general medical facilities and add to the global data on the same subject.…”
Section: Introductionmentioning
confidence: 99%
“…15 These studies have also shown differences in the nature and extent of stigma attached to the various psychiatric illnesses by the different cadres of medical health workers. [15][16][17][18][19][20][21][22] This study therefore aimed to determine the knowledge of and attitude towards mental illness among hospital staff in general medical facilities. This information would be useful in the formulation of policy for training, management and service delivery on mental health issues in general medical facilities and add to the global data on the same subject.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the changes are not caused by the aging process, but by disease, the environ-ment, and lifestyles 7) . Some of the changes caused by these factors may be prevented or slowed down by taking action.…”
Section: Issues In General Healthmentioning
confidence: 99%
“…Existe un consenso generalizado acerca de que las personas de edad con síndrome de Down en particular y con discapacidad intelectual (DI) en general experimentan el mismo rango de necesidades para el cuidado de la salud que las personas de la población general, sin embargo, la frecuencia de tales problemas se incrementa en las primeras (Evenhuis et al, 2000). Así, diversos autores (Glasson et al, 2014;Hermans y Evenhuis, 2014) señalan que las personas con SD son más propensas a desarrollar la demencia tipo Alzheimer, especialmente a partir de los 35 años, siendo el foco principal en este campo de la investigación la asociación entre los determinantes genéticos, los marcadores biológicos y las limitaciones en el funcionamiento de dominios cognitivos específicos (Tyrrell et al, 2001).…”
Section: Introductionunclassified